Averrhoa bilimbi (Belimbing Wuluh) Leaves Extract Evaluation as Anti-Cariogenic Mouthwash - Nugraheni, Oktavia Dwi; Haerussana, Ayu Nala El Muna (Jurnal Riset Kesehatan, 2024)
The practice of using mouthwash has become increasingly common as people have become more aware of the importance of oral hygiene in preventing dental issues. In order to mitigate any potential risks associated with alcohol-based mouthwashes, researchers are exploring natural sources of anti-cariogenic compounds. This study aimed to assess the effectivity of Averrhoa bilimbi leaf extract as an ingredient in mouthwash formulations, as the use of Averrhoa bilimbi leaves is still limited. The evaluation of the mouthwash included a thorough examination of its antibacterial activity, viscosity, density, pH, and organoleptic qualities. The results indicated that formula with 30 grams extract (F3) was the most effective, exhibiting more robust antibacterial properties, appropriate viscosity and density, and a pH level similar to that of a solution. F3 resulted in an effectiveness of 41.67%, 1.36 cPs for viscosity, 1.0785 mg/l for density, pH of 5.25+0.006, organoleptically liquid, mint odor, and blackish brown clear color. Based on these findings, it appears that Averrhoa bilimbi leaf extract could be a promising ingredient in mouthwash formulations.